Impact of simulation‐based learning on immediate outcomes of temporary haemodialysis catheter placements by nephrology fellows. Issue 10 (24th September 2018) - Tan, Ru Yu; Lee, Kian Guan; Gan, Shien Wen Sheryl; Li, Huihua; Yeon, Wenxiang; Pang, Suh Chien; Teh, Swee Ping; Htay, Htay; Teo, Su Hooi; Kwek, Jia Liang; Tok, Pei Loo; Poh, Cheng Boon; et al.
Summary at a Glance: Improving procedural competency by simulation training may be associated with less complications. This retrospective study supports the use of structured training over the traditional apprentice model of insertion of acute haemodialysis catheters in a small cohort of trainees. ABSTRACT: Aim: Traditional apprenticeship model (AM) of teaching in invasive procedures such as temporary haemodialysis catheter (THDC) insertion can result in propagation of errors and complications. Simulation‐based learning (SBL) offers standardization of skills and allows trainees to repeatedly practice invasive procedures prior to performing them on actual patient. Methods: Retrospective cohort study of first‐, second‐ and third‐year Nephrology Fellows from a tertiary teaching hospital from September 2008 to September 2015. The intervention group ( n = 9) received simulation training in ultrasound‐guided THDC placement. The historical control group ( n = 12) received training through traditional AM. The primary and secondary outcomes were the immediate complications and success rates of THDC insertion. Results: A total of 2481 THDCs were placed in 1787 patients. Success rate of internal jugular THDC placement for AM vs. SBL Fellow was 99.8% versus 100% ( P = 0.90), while the success rate for femoral THDC placement was 99.6% versus 99.2% ( P = 0.53). SBL Fellows reported fewer overall peri‐procedure complications (8.3% vs. 11.2%, P = 0.02) and mechanical complications (1% vs. 2.4%, P = 0.02) compared to AM Fellows. The rate of reported technical difficulty was similar (7.5% vs. 9.2%, P = 0.17). After adjusting for side and site of THDC placement, body mass index and laboratory indices, THDC inserted by AM Fellows were independently associated with increased overall peri‐procedure complications (OR = 1.396, 95% CI: 1.052–1.854, P = 0.02) and mechanical complications (OR = 2.481, 95% CI: 1.178–4.810, P = 0.02). Conclusions: Simulation‐based learning was associated with lower procedure related complications and should be an integral component in the teaching of procedural skills in Nephrology.